Language play and norm deviation in art and advertising in Old Tiflis: Occasionalism as a didactic tool - Simyan, Tigran (Glottodidactica, 2026)
The present article employs a diachronic linguistic landscape (LL) perspective to examine Russian-language advertising in late nineteenth- and early twentieth-century Tbilisi (Old Tiflis) as evidence of lived multilingualism and historically situated language competence. The analysis encompasses historically documented verbal and visual “texts in space”, primarily preserved in Armenian literary discourse, complemented by paintings depicting urban signage. The study examines the interaction of Russian, as the imperial lingua franca, with Armenian, Georgian and other local languages within a multiethnic urban environment. Methodologically, it combines semiotic metalanguage with Bakhtin’s theory of speech genres and the triad of normusus- occasionalism to classify deviations from standard Russian and interpret their pragmatic and cultural functions. The findings demonstrate that pervasive orthographic, grammatical, syntactic and stylistic “errors” cannot be reduced to illiteracy; rather, they index language contact, interference, sociolectal variation and a carnivalesque urban ethos conceptualised as “Tiflis Esperanto” and preserved in cultural memory. The article finally contends that such norm distortions possess a considerable didactic potential. At B2 level and above, the progression from occasionalism through usage to norm serves to enhance register awareness and facilitates the acquisition of spelling, grammar, syntax and pragmatic conventions. This process is facilitated by culturally grounded cognitive disruption.